PENGARUH DANA PIHAK KETIGA, SUKU BUNGA SIMPANAN, KECUKUPAN MODAL, RISIKO KREDIT DAN SUKU BUNGA KREDIT TERHADAP PROFITABILITAS (Studi Kasus Pada Industri Perbankan yang Terdaftar di Bursa Efek Indonesia tahun 2015-2017) - Dina Sustiana; Jeni Susyanti; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTFor three years starting in the 2015-2017 period Profitability has fluctuated. In this study the author will discuss about third party funds, deposit rates, capital adequacy, credit risk and credit interest rates that can affect profitability. The purpose of this study is (1) To determine the effect of third party funds on profitability (2) To determine the effect of deposit interest rates on profitability (3) To determine the effect of capital adequacy on profitability (4) To determine the effect of credit risk on profitability (5) know the effect of credit interest rates on profitability.This thesis research uses a type of quantitative approach research; this study takes samples from the population using purposive sampling technique. By using two types of variables, namely Dependent Variables (dependent variables) and independent variables (independent variables). The results of this study are third party funding variables have a positive and not significant effect on profitability, deposit interest rates have a negative and not significant effect on profitability, capital adequacy variables have a positive and not significant effect on profitability, credit risk variables have a negative and significant effect on profitability, variable credit interest rates have a negative and significant effect on profitability Keywords: Third party funds, deposit interest rates,